2019
DOI: 10.1111/cid.12726
|View full text |Cite
|
Sign up to set email alerts
|

The application of a newly designed L‐shaped titanium mesh for GBR with simultaneous implant placement in the esthetic zone: A retrospective case series study

Abstract: Background To our acknowledgment, there were limited clinical studies about the guided bone regeneration (GBR) for both vertical and horizontal augmentation at the same time using titanium mesh (Ti‐mesh) with simultaneous implant placement in the esthetic zone. Meanwhile, studies that specially evaluate resorption and long‐term stability of the augmented labial bone after loading were also rare. Therefore, this study introduced a newly designed L‐shaped Ti‐mesh used for GBR with simultaneous implant placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 51 publications
3
67
0
1
Order By: Relevance
“…In the patients with a small or medium alveolar bone defect requiring both horizontally and vertically bone augmentation, the mean horizontal and vertical bone augmentation reached (3.10 ± 2.06) and (3.61 ± 1.50) mm, which gained enough three-dimensional bone volume, and achieved a 93.75% success rate of implantation. 28 A systematic review that analyzed simultaneous implantation after bone augmentation with titanium mesh demonstrated the survival rate of implants placed into native bone and that placed immediately after bone grafting is similar, and in the statistics of this article, no implant failure is observed. 37 Therefore, it can be concluded that under the premise of indications, the immediate implantation after bone augmentation with titanium mesh is a feasible and favorable treatment strategy.…”
Section: Current Application Of Titanium Mesh In Bone Augmentationmentioning
confidence: 64%
See 3 more Smart Citations
“…In the patients with a small or medium alveolar bone defect requiring both horizontally and vertically bone augmentation, the mean horizontal and vertical bone augmentation reached (3.10 ± 2.06) and (3.61 ± 1.50) mm, which gained enough three-dimensional bone volume, and achieved a 93.75% success rate of implantation. 28 A systematic review that analyzed simultaneous implantation after bone augmentation with titanium mesh demonstrated the survival rate of implants placed into native bone and that placed immediately after bone grafting is similar, and in the statistics of this article, no implant failure is observed. 37 Therefore, it can be concluded that under the premise of indications, the immediate implantation after bone augmentation with titanium mesh is a feasible and favorable treatment strategy.…”
Section: Current Application Of Titanium Mesh In Bone Augmentationmentioning
confidence: 64%
“…Zhang et al showed that for a single anterior tooth defect, during the 41-month follow-up period after implant placement, the labial bone plate experienced an average of −0.81 ± 1.00 mm vertical absorption, which bone upon the implant absorbed at mean of 0.13 ± 1.19 mm in horizontal dimension. 28 And the study conducted by Poli et al showed that for a large range of GBR with titanium, the mesial and distal bone resorption were at an average of 1.743 ± 0.567 and 1.913 ± 0.71 mm, respectively, during the 88-month follow-up period after implantation. 34 Therefore, the possibility of bone resorption also needed to be considered when performing bone augmentation with titanium mesh.…”
Section: Mechanical Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…In our previous studies, it was confirmed that the L‐shaped titanium mesh could provide both horizontal and vertical augmentations for alveolar bone in GBR 6 . At the longest follow‐up of 41 months, the thickness of the remaining labial bone at the top of the implant was approximately 2.24 mm, and there was still a vertical bone mass of 1.13 mm above the top of the implant.…”
Section: Introductionmentioning
confidence: 70%